Pengembangan Women Empowerment Class untuk Menigkatkan Kesetaraan Gender di Pesantren Sirojul Hikmah Bojonegoro - Djovana, Amalya El Fatihah; Khusumadewi, Ari (Jurnal Bimbingan dan Konseling Islam, 2021)
Gender equality bocome an endlessly topic tobe discussed since there are so many problems which are still discussed excisting. In this study, the islamic boarding school became an interesting subject whare the existence of gender equality is believed as a new value which was voiced the western culture. It also became a concern that gender equality may break the establishment of cultures contruction. In fact, women is more experiencedin gender inequlity than men. This can be seen in various scopes and sectors. The purpose of this research is to answer and providing the solution for existing gender equality problems. Bydeveloping woman class to produce a training device. Which can be used to give conseling service at school. The method of this research is descriptive qualitative by using Intructuralational Development Institute (IDI). The subjects of this research were students atMadrasah Aliyah Islamis Boarding School Sirojul Hikmah Bojonegoro. The result of the content and material test carried out by the experts, mentioned that each of them has a high percentage with good information and no need to be revised. The result of this research found that the conseling devices which was known and could be applied in Islamic Boarding School.